2012
DOI: 10.1590/s1806-00132012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Dor pós-operatória em pacientes submetidos à craniotomia eletiva

Abstract: RESUMO Objetivo: Identificar a presença de dor em pacientes submetidos à craniotomia eletiva e a localização dela. Método: Pesquisa descritiva, longitudinal com abordagem quantitativa. A casuística constituiu-se de 92 pacientes submetidos à craniotomia eletiva. Resultados: Os dados demonstram que 60,9% dos pacientes eram do sexo feminino, 56,5%, solteiros e 34,8%, oriundos da capital. No primeiro dia pós-operatório 63% dos pacientes queixavam-se de dor, e a cefaleia foi a principal queixa em 39,1% dos entrevis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…It was also indentified that most medical charts had no records on pain intensity by the multidisciplinary team, thus confirming our findings. When pain was recorded, in most cases this was done by physicians and in few patients by the nursing team 9 . It is known that in clinical practice opioids and NSAIDS are broadly used to treat and relieve POP, however their analgesic efficacy varies according to potency, duration of their effect and possibility of inducing undesirable effects which limit their continuity.…”
Section: Discussionmentioning
confidence: 99%
“…It was also indentified that most medical charts had no records on pain intensity by the multidisciplinary team, thus confirming our findings. When pain was recorded, in most cases this was done by physicians and in few patients by the nursing team 9 . It is known that in clinical practice opioids and NSAIDS are broadly used to treat and relieve POP, however their analgesic efficacy varies according to potency, duration of their effect and possibility of inducing undesirable effects which limit their continuity.…”
Section: Discussionmentioning
confidence: 99%
“…It was identified that 90.2% of cases had no pain recording, and the few existing records were made by physicians. A study evaluating pain in patients submitted to craniotomy has identified similar data 15 . Adequate pain evaluation and recording are critical to prevent surgical complications and patients' distress.…”
Section: Discussionmentioning
confidence: 85%
“…The history of previous surgeries may trigger anxiety and, consequently, reflect in increased preoperative pain intensity 12 . Pain worsening brings several damages to patients, such as increased heart work, decreased blood offering to tissues and increased distress 13 , which may also be noxious for patients' clinical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients had preoperative moderate, pulsing and frontal headache. Studies evaluating the prevalence of pain in patients submitted to craniotomy had high frequency of preoperative pain with similar characteristics [8][9][10][11][12][13][14] . The presence of aneurysm might have influenced pain pulsing character and frontal location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation